Infection control measures for public transportation derived from the flow dynamics of obstructed cough jet. (June 2022) - Wang, C.T.; Xu, J.C.; Chan, K.C.; Lee, H.H.; Tso, C.Y.; Lin, Carol S.K.; Chao, Christopher Y.H.; Fu, S.C.
Abstract: During the COVID-19 pandemic, WHO and CDC suggest people stay 1 m and 1.8 m away from others, respectively. Keeping social distance can avoid close contact and mitigate infection spread. Many researchers suspect that suggested distances are not enough because aerosols can spread up to 7–8 m away. Despite the debate on social distance, these social distances rely on unobstructed respiratory activities such as coughing and sneezing. Differently, in this work, we focused on the most common but less studied aerosol spread from an obstructed cough. The flow dynamics of a cough jet blocked by the backrest and gasper jet in a cabin environment was characterized by the particle image velocimetry (PIV) technique. It was proved that the backrest and the gasper jet can prevent the front passenger from droplet spray in public transportation where maintaining social distance was difficult. A model was developed to describe the cough jet trajectory due to the gasper jet, which matched well with PIV results. It was found that buoyancy and inside droplets almost do not affect the short-range cough jet trajectory. Infection control measures were suggested for public transportation, including using backrest/gasper jet, installing localized exhaust, and surface cleaning of the backrest. Highlights: Keeping social distance in public transportation is difficult, meaning high risk. Flow dynamics of cough jet in a cabin environment is studied by PIV technique. Backrest and gasper jet can be compensation for not keeping social distance. Localized exhaust under each seat is suggested to timely remove bulk aerosols. A universal model is proposed to predict the obstructed cough jet trajectory.